EXPERIENTIAL VALUE TOWARD BEHAVIORAL INTENTION OF LOCAL FOOD THROUGH CONSUMER ATTITUDE: INSIGHT FROM GEN Z'S IN JAKARTA - Tjokrosaputro, Miharni (Universitas Brawijaya, Indonesia, 2023)
Recently, there has been an increase in public excitement for culinary experiences, including local cuisine exploration. The wide range of Indonesian cultures significantly impacts the variety of local food variations, which must be maintained. However, Indonesian Gen Z (27.94% of the overall population) prefers food from other cultures to their own. So, this study examines the role of experiential value as an antecedent of Generation Z's attitude to local food and its influence on behavioral intentions. This research will examine the role of consumer attitude as a mediator in the relationship between values on the behavioral intentions of Gen Z in Jakarta towards local food. The research was conducted using convenience sampling through a questionnaire by a cross-sectional survey. The data were obtained from 130 respondents and processed further with SmartPLS. The test results show that the experience value of Gen Z has a positive and significant effect on consumers' behavior and behavioral intentions toward local food. Thus, Gen Z's behavior has a positive and significant impact on the behavioral intention of Gen Z toward local food. Experiential value has a positive effect on the behavioral intention of Gen Z towards local food, mediated by consumer attitudes. This research provides input for local food entrepreneurs about the importance of experiential value through the dimensions of customers' return on investment, aesthetics, and cheerfulness. The experiential value positively influences Gen Z's attitude and behavioral intentions toward local food. For academics, this research can expand and enrich research in the food industry, especially local food.